2022
DOI: 10.1002/jssc.202100991
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and selective LC‐MS/MS for the determination of tolperisone and etodolac in human plasma and application to a pharmacokinetic study

Abstract: Tolperisone and etodolac were proven to have synergistic effect for patients of acute low back pain associated with musculoskeletal spasm. In this work, a specific, highly sensitive and reproducible analytical method was developed and validated for the simultaneous determination of tolperisone and etodolac in human plasma using liquid chromatography-tandem mass spectrometric technique. Liquid-liquid extraction was optimized for sample preparation. Zorbax C 8 column (3.5 μm, 50 × 4.6 mm) was used, carrying a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Fig. 1 Chemical structure of TOLP not accessible in most laboratories for routine analysis [4][5][6][7][8]. Potentiometric ion-selective electrode (ISE) is a cost-effective analytical technique that can be employed for performing measurements in colored and turbid solutions [9,10].…”
Section: Graphical Abstractmentioning
confidence: 99%
See 2 more Smart Citations
“…Fig. 1 Chemical structure of TOLP not accessible in most laboratories for routine analysis [4][5][6][7][8]. Potentiometric ion-selective electrode (ISE) is a cost-effective analytical technique that can be employed for performing measurements in colored and turbid solutions [9,10].…”
Section: Graphical Abstractmentioning
confidence: 99%
“…Literature review revealed that some analytical techniques such as chromatographic methods [3][4][5][6] and UV Spectrophotometry [7,8] had been reported for estimation of TOLP in individual dosage forms and combination with other drugs. Even though good results were achieved, the proposed techniques are solvent and time-consuming and use costly instruments which are…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the classic methods of purine detection, such as ion exchange chromatography and reversed-phase-high-performance liquid chromatography (RP-HPLC) were not superior in sensitivity and specificity [13,14]. Therefore, LC-MS was considered and preferred owing to the complexity of the compounds in plasma [15,16]. Yamaoka et al [17] have established a reproducible and accurate ultra-performance LC (UPLC)-MS method to simultaneously quantify 23 nucleotides, which was not suitable for large-scale detection due to its long running time, and the switching of positive and negative ion modes would bring fluctuations in sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…However, the classic methods of purine detection, such as ion exchange chromatography and reversed‐phase–high‐performance liquid chromatography (RP‐HPLC) were not superior in sensitivity and specificity [13, 14]. Therefore, LC‐MS was considered and preferred owing to the complexity of the compounds in plasma [15, 16]. Yamaoka et al.…”
Section: Introductionmentioning
confidence: 99%